Impact of prenatal hypoxia on the development and behavior of the rat offspring - Piešová, Michaela; Koprdová, Romana; Ujházy, Eduard; Kršková, Lucia; Olexová, Lucia; Morová, Martina; Senko, Tomáš; Mach, Mojmír (Physiological research, 2020)
The healthy development of the fetus depends on the exact course of pregnancy and delivery. Therefore, prenatal hypoxia remains between the greatest threats to the developing fetus. Our study aimed to assess the impact of prenatal hypoxia on postnatal development and behavior of the rats, whose mothers were exposed to hypoxia (10.5 % O2) during a critical period of brain development on GD20 for 12 h. This prenatal insult resulted in a delay of sensorimotor development of hypoxic pups compared to the control group. Hypoxic pups also had lowered postnatal weight which in males persisted up to adulthood. In adulthood, hypoxic males showed anxiety-like behavior in the OF, higher sucrose preference, and lower levels of grimace scale (reflecting the degree of negative emotions) in the immobilization chamber compared to the control group. Moreover, hypoxic animals showed hyperactivity in EPM and LD tests, and hypoxic females had reduced sociability compared to the control group. In conclusion, our results indicate a possible relationship between prenatal hypoxia and changes in sociability, activity, and impaired emotion regulation in ADHD, ASD, or anxiety disorders. The fact that changes in observed parameters are manifested mostly in males confirms that male sex is more sensitive to prenatal insults.
Keywords: Behavior, Animal; modely nemocí na zvířatech; Prenatal Exposure Delayed Effects; Male; Rats, Wistar; Social Interaction; zpožděný efekt prenatální expozice; gestační stáří; acidobazická rovnováha; Maze Learning; sexuální faktory; Gestational Age; sociální interakce; Pregnancy; těhotenství; Acid-Base Equilibrium; Age Factors; Food Preferences; preference v jídle; mužské pohlaví; potkani Wistar; úleková reakce; bludiště - učení; senzorimotorický kortex; Animals; ženské pohlaví; zvířata; pohybová aktivita; Sex Factors; Disease Models, Animal; věkové faktory; hypoxie plodu; Motor Activity; chování zvířat; Fetal Hypoxia; Sensorimotor Cortex; Reflex, Startle; Female